FISHER INCOME CONTRIBUTION 0FF FISHING TOWARD FISHER TOTAL INCOME IN TANJUNG KURAS VILLAGE SUNGAI APIT DISTRICT SIAK REGENCY RIAU PROVINCE - Fajri, Junedi; Hamid, Hamdi; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research did in Tanjung Kuras Village, Sungai Apit District, Siak Regency Riau Province at 1th Juny until 27th Juny 2015. The purpose do this research is to know the other type of business that conducted fisher and to know how many big income contribution off-fishing toward fisher total income.The data was collected in the census, where all the fishermen in the Tanjung Kuras village as object for questioning. The data obtained in this study were analyzed with descriptive analysis. The using data are primer data and secunder data.The type of alternative activities on coastal fishing communities in the Tanjung Kuras village include motorcycle taxis, oil palm workers, masons, and as haul market worker and the contribution from off-fishing toward fisher total income is 19,5%.Key words : contribution, off-fishing income